Macronutrient content of pooled donor human milk before and after Holder pasteurization - Pasqua Piemontese; Domenica Mallardi; Nadia Liotto; Chiara Tabasso; Camilla Menis; Michela Perrone; Paola Roggero; Fabio Mosca (BMC Pediatrics, 2019)
Abstract Background Donor human milk (DHM) is the best alternative for preterm infants when their own mother’s milk is unavailable. DHM should be pasteurized to guarantee microbiological safety; however, this process can influence the macronutrient content. The aim of this study was to investigate the effect of Holder pasteurization (HoP) on DHM macronutrient content. Methods Protein, lactose, lipids (g/100 ml) and energy (kcal/100 ml) of DHM pools were analysed before and after HoP (62.5 °C for 30 min) using mid-infrared spectroscopy (HM analyser Miris AB®). The mean macronutrient content before and after HoP was compared by paired t-test. The percentage decreases (Delta%) were calculated. Results The change in macronutrient content of 460 pools was determined. Protein, lipids and lactose decreased significantly after HoP (0.88 ± 0.20 vs 0.86 ± 0.20 and 2.91 ± 0.89 vs 2.75 ± 0.84 and 7.19 ± 0.41 vs 7.11 ± 0.48 respectively). The Delta% values were − 2.51 ± 13.12, − 4.79 ± 9.47 and − 0.92 ± 5.92 for protein, lipids and lactose, respectively (p ≤ 0.001). Conclusion This study confirms that the macronutrient content of DHM, especially in terms of lipids and protein, is reduced after HoP. Therefore, in order to perform a tailored fortification of DHM, the clinicians need to be aware of the somewhat diminished nutrient content of DHM.